Production Of Biolubricant Based On Jatropha Curcas Oil And Linear Alcohol Abstract - Adriani, Nina; Salimon, Prof.Dr. Jumat (Jurnal Zarah, 2013)
The use of oils and fats for lubrication purposes has been practiced for many years. This is starting that realized since the mineral oil in a limited number. In this research, the production of biolubricant based plant oil is Jatropha Curcas oil and linear alcohol. Oil produced from the fruits is 44.30%. However, oxidative stability and low pour point are problem for biolubricant. The method used to overcome this problem is epoxidation process and ring opening. Epoxidation process successfully carried out by testing the oxyrane value and also FTIR analysis, where the peak of alkenes is 3007 cm-1. Epoxy peak appeared at 843 and 824 cm-1, which is testament to the success of epoxy ring is formed. Ring opening proved successful with FTIR analysis of the appearance of hydroxyl groups at the peak of 3444 cm-1, the peak of ether in 1097 cm-1, and the loss of epoxy peak. Bioubricant which is produced in the form of alcohol ether is to produce five types of biolubricant, which are decanol ether, dodecanol ether, tetradecanol ether, hexadecanol ether and octadecanol ether. 1H dan 13C  NMR analysis is also succeeded in proving the presence of key functional groups for the fifth type of biolubricants. In terms of viscosity and flash point, lubricant successful enhanced oil-based plants, but not succeded to reduce the pour point.